The Influence of Current Ratio, Debt to Equity Ratio, and Net Profit Margin on Stock Prices (In the Mining Sector Registered in LQ 45 Year 2018-2022) - Aditya Dwi Okta S.; Meli Nur'Aeni; Fitria Dewi S.; Rawi Rawi (Pusat Publikasi Nusantara, 2024)
This research aims to determine the influence of the current ratio, debt to equity ratio, and net profit margin on stock prices. This type of research is quantitative with a descriptive approach. The population in this research is LQ 45 trading and manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique uses purposive sampling. The type of data used is secondary data. The data analysis technique in this research uses classical assumptions and multiple linear regression analysis. The research results show that the current ratio, debt to equity ratio, and net profit margin have a positive and significant effect on stock prices.